2011
DOI: 10.1017/s1833367200001280
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility in management education: Current status in Spanish universities

Abstract: In the context of education for sustainable development, the purpose of this paper is to report on the findings of a study in Spain into the extent to which corporate social responsibility (CSR) is taught in management schools. The study makes an exploratory and descriptive web-content analysis of the curriculum and subjects on Business and Management degrees at all universities in Spain. Our findings show that a high percentage of universities include CSR-related subjects on their curriculum. CSR content is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 32 publications
1
36
0
11
Order By: Relevance
“…Such a type of course is the, more or less, classical MBA program and could not be linked to today's changed business environment with the increased importance of CSR. The results achieved in our study support the findings of Seto-Parnies et al [64] who analyzed the extent to which corporate social responsibility (CSR) is taught in management schools and stated that although many universities have embedded CSR subjects, the CSR content is by no means fully developed. These statements support our second (H2) hypothesis that there is a substantial lack of CSR integration into professional business and administration training and somehow support our first hypothesis (H1) that CSR is integrated into the training of business and management professionals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Such a type of course is the, more or less, classical MBA program and could not be linked to today's changed business environment with the increased importance of CSR. The results achieved in our study support the findings of Seto-Parnies et al [64] who analyzed the extent to which corporate social responsibility (CSR) is taught in management schools and stated that although many universities have embedded CSR subjects, the CSR content is by no means fully developed. These statements support our second (H2) hypothesis that there is a substantial lack of CSR integration into professional business and administration training and somehow support our first hypothesis (H1) that CSR is integrated into the training of business and management professionals.…”
Section: Discussionsupporting
confidence: 87%
“…While researchers from Western countries sometimes show the ongoing withdrawal of enterprises from the very idea of CSR and present themselves to stakeholders by imitating CSR as one of the marketing tools [3][4][5][6], or even lobbying [7] (pp. [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], it is becoming a clear trend in post-Soviet countries. Therefore, attention is paid to the fact that the implementation of CSR should be oriented not towards charity, marketing, and public relations, but should first and foremost be understood as social responsibility towards stakeholders [8].…”
Section: Introductionmentioning
confidence: 99%
“…Desde esta argumentación, la RSU se relaciona con la construcción ciudadana desde el impacto que la primera pueda provocar en la segunda, y en ella las universidades deben asumir una postura y un rol protagónicos, conjuntamente con las acciones dirigidas a promover la igualdad de oportunidades, la maximización de talentos en la vida universitaria y la conciliación de su estudio con la vida personal. Así lo ratifican investigaciones que insisten en cómo las percepciones del estudiantado, así como las experiencias acometidas con respecto a RSU en sus estudios universitarios, representan un valioso input para las universidades (Gaete & Bratos, 2012;Peralta, 2012;Selvaratnam, 2013;Setó, Domingo & Rabassa, 2011;Vázquez, Aza & Laneso, 2014), deduciéndose de todo ello el hecho de que resulta necesario desarrollar por parte de las universidades nuevos métodos y marcos que ayuden a aplicar la RSU en el mundo global (Audebrand, 2010;Navarro et al, 2010;Noguera, Moncayo & Martí-Vilar, 2014;Vasilescu et al, 2010) en términos de respeto a la diversidad, igualdad de oportunidades, distribución equitativa de recursos y procesos transparentes y democráticos de elección, participación y vivencia local y global.…”
Section: Responsabilidad Social Universitaria Como Marco De Análisisunclassified
“…Setó‐Pamies et al . () made an exploratory and descriptive web content analysis of the curricula and subjects in business and management degrees in all universities in Spain. Their findings showed that 17% of the 62 business and management undergraduate degrees offered during 2006/2007 provided CSR and ethical stand‐alone subjects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, it is important to take advantage of the great opportunity offered by the EHEA reforms so that the incorporation of CSR and business ethics within future organizational management undergraduate degrees can be properly debated and dealt with (Setó‐Pamies et al . ).…”
Section: Introductionmentioning
confidence: 97%